التحكيم رديفاً للقضاء في حل المنازعات - دراسة فقهية - Abu Lail, Mohammad (Jordan Journal of Islamic Studies, 2020)
Arbitration is considered as one of the basic means that has been legislated by Islam to resolve the people's disputes. Usually the resolutions of the arbitration are fast, guarantee the rights, respect the essence of justice and reduce the level of the controversy. Today, arbitration plays a vital role in resolving the international disputes such as the economic, political and local disputes as long as its effect upon the resolution of the internal disputes. This study highlights on the arbitration role in resolving the disputes as along with judiciary through showing the advantages of the arbitration and explain the relationship between arbitration and judiciary. And clarify its areas and its implications in jurisprudence. This study found out that the arbitration has a pivotal role in resolving the disputes resulting from the contractual and non-contractual relationships and the disputes resulting from the people in their natural and moral capacity, both internally as well as externally The study has shown the jurisprudence has taken the lead in explaining the terms and effects of the arbitration.